2022
DOI: 10.1007/s11126-022-09981-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Growth and Resilience among American Medical Students during the COVID-19 Pandemic

Abstract: The ongoing COVID-19 pandemic has caused significant psychological impact on medical professionals, including medical students, many who have been caring for patients on the frontlines. Understanding how medical students perceive their stressful life experiences is important as the mental health of these future physicians directly impacts their ability to care for patients. We assessed for post-traumatic growth and resilience in the face of traumatic events among a cohort of medical students that attended a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
2
14
0
2
Order By: Relevance
“…College students, as a special group, may have experienced a greater psychological impact from the COVID-19 pandemic, which could be due to increased academic performance concerns in online learning and drastic reduction social activities [ 11 ]. According to previous studies, college students are more vulnerable to various impacts from sudden changes in the COVID-19 pandemic [ 17 ]. These constant COVID-19 pandemic-related stressors may adversely affect the sleep quality of medical students.…”
Section: Introductionmentioning
confidence: 99%
“…College students, as a special group, may have experienced a greater psychological impact from the COVID-19 pandemic, which could be due to increased academic performance concerns in online learning and drastic reduction social activities [ 11 ]. According to previous studies, college students are more vulnerable to various impacts from sudden changes in the COVID-19 pandemic [ 17 ]. These constant COVID-19 pandemic-related stressors may adversely affect the sleep quality of medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Rezultaty badań wyglądają obiecująco, ponieważ znacząca przewaga pozytywnych metod radzenia sobie ze stresem jest korzystnym zjawiskiem w kontekście reakcji na światowy kryzys. Przewagę pozytywnych metod nad negatywnymi stwierdzono też w innych dostępnych badaniach, zarówno polskich [26], jak i przeprowadzonych wśród studentów z innych kręgów kulturowych [27,28]. Czynnikami, które najmocniej oddziałują na ten wynik, są aktywne działania, wykorzystanie wsparcia informacyjnego oraz planowanie -są to cechy, jakimi charakteryzują się odporne i dobrze zaadaptowane społeczeństwa [29].…”
Section: Dyskusjaunclassified
“…Pozytywne nastawienie, powszechne wśród studentów, może mieć swoje źródło w intensywnym poszukiwaniu kontaktu z innymi oraz w poszukiwaniu wsparcia. Studenci w dużym stopniu opierali się na swojej sieci społecznej [28], co było możliwe, gdyż w tej grupie wiekowej kontakt online jest równie wartościowy jak kontakt na żywo i mógł stanowić substytut bezpośredniej relacji. Relacje z rodziną również stanowiły istotny element adaptacji do stresujących okoliczności [31].…”
Section: Dyskusjaunclassified
“…These constant COVID-19 pandemic-related stressors may adversely affect the sleep quality of medical students. During the COVID-19 pandemic, the mental health of college students has been affected to varying degrees (15). Satici B et al found that fear of COVID-19 may lead to severe psychological problems in individuals, which in turn may reduce people's satisfaction with their lives during the COVID-19 pandemic (16).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research reported indicate that the COVID-19 pandemic and dramatic changes in learning styles pose signi cant threats to medical students' physical and mental health, such as fear of the COVID-19 pandemic. The further development of COVID-19 fear may lead to the occurrence of stress, depression, anxiety psychological disorders and endocrine disorders, growing fears of COVID-19 can trigger a range of serious physical dysfunctions, such as insomnia(15). Research had shown that fears of COVID-19, including fear of the future and fear of contracting the COVID-19, as well as concerns about their own health, which is linked to poor mental health problems (46).…”
mentioning
confidence: 99%